2021
DOI: 10.3390/ijerph18105313
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of National Tobacco Cessation Services among Female Smokers and the Need for a Gender-Responsive Approach

Abstract: Despite the steadily increasing prevalence of female smoking, gender-responsive tobacco cessation services have not been widely provided worldwide. The purpose of this study is to identify factors associated with the use of tobacco cessation services among female tobacco product users in Korea from a national perspective. We performed a logistic regression analysis using data from 663 female smokers; 11.0% of female smokers had used government-supported smoking cessation services. A logistic regression model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Regarding gender differences in smoking cessation, women are more likely to have difficulty maintaining long-term abstinence from smoking than men including those with even moderate addiction [6], those between the ages of 30 and 55 (approximately) [6], those with some smoking cessation therapy [7,8], and those who consume alcohol [9]. Some arguments have been put forward stating that the gender differences observed in clinical trials [10] cannot be translated into real-world settings [11], but a recent study on the utilization of National Tobacco Cessation Services among female smokers also suggested that further research considering gender-specific tobacco cessation support was needed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding gender differences in smoking cessation, women are more likely to have difficulty maintaining long-term abstinence from smoking than men including those with even moderate addiction [6], those between the ages of 30 and 55 (approximately) [6], those with some smoking cessation therapy [7,8], and those who consume alcohol [9]. Some arguments have been put forward stating that the gender differences observed in clinical trials [10] cannot be translated into real-world settings [11], but a recent study on the utilization of National Tobacco Cessation Services among female smokers also suggested that further research considering gender-specific tobacco cessation support was needed [12].…”
Section: Introductionmentioning
confidence: 99%